An Overview on Vertical Farming (International Journal of Innovative Research in Computer Science & Technology, 2022)
Vertical farming methods allow for the  effective use of space by growing fresh food vertical in  dissimilar layer piled atop each other’s. Vertical farming  techniques do not require sunshine or soil since the  atmosphere is entirely regulated. Only one hand, vertical  farming, with its higher crop yield per square metre utilised  than conventional farming, might assist to provides  nutritious diets for world's expanding population; on the  other hand, it may provide the possibility to grow foods in  the climatically challenged locations. However, atypical  growth circumstances, as well as the entire vertical farming  systems, might well be considered unsustainable. As a result,  it's vital to understand if vertical farming techniques are  acceptable to customers. This is the first research to look at  how three distinct vertical farming methods are accepted by  customers. The information was gathered in February 2018  through an online poll of 482 German customers. Structural  equation modelling is used to identify the factors that  influence customer acceptability of vertical farming systems.  The findings show that consumer adoption of vertical  farming systems is mostly driven by perceptions of  sustainability. The greater the system's size, the more likely  it is to be regarded sustainable. Consumers clearly detect  things like scale ecologies.
Keywords: Agriculture; Farming; Production; Population; Vertical